Изучение взаимосвязи "состав-свойство" тонкопленочных силикатных материалов - Иконникова К. В. Ксения Владимировна; Козик В. В. Владимир Васильевич; Борило Л. П.; Иконникова Л. Ф. Любовь Федоровна (2000, 2000)
В фонде НТБ ТПУ отсутствует